Facilitators and Barriers for Effective Staff Work in Swedish National Governmental Crisis Response to the COVID-19 Pandemic. (1st April 2023) - Westman, Anja; Hugelius, Karin; Weinstein, Eric; Kurland, Lisa
Abstract: Objectives: The coronavirus disease (COVID-19) crisis response in Sweden was managed foremost by a collaboration of several national agencies. Normally, their strategical and operational collaboration is limited, but the pandemic required new and unfamiliar collaborations. This study aimed to clarify the facilitators and barriers of perceived effective staff work within and between 4 national agencies. Methods: A qualitative study of 10 participants with leading roles within the 4 national agencies' crisis organization was conducted via snowball sampling. The participant interviews were conducted between August and November 2020 and analyzed using content analysis. Results: Four categories emerged from the analysis: individual characteristics, intra-agency organization, interorganizational collaboration, and governmental directives. Subcategories crystallized from the data were analyzed and divided into factors for facilitating or to function as barriers for effective staff work. Conclusion: Individual factors such as attitude and approach were important for perceived effective staff work as well as clear mandates and structure of the organization. Barriers for perceived effective staff work include lack of network, the complexity of the mission and organizational structures, as well as lack of preparations and unclear mandates. Although flexibility and adaptability are necessary, they cannot always be planned, but can be incorporated indirectly by selecting suitable individuals and optimizing organizational planning.